EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15387632 ZenodoArchiveConcept: 15387631 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1117 2405685:SB7G3I83
Keywords: _r:AddedByMyEducationEvidence

AI in the Classroom: A rapid evaluation of AI-generated lesson plans in Islamabad’s public schools - Aslam, Nawaz; Qureshi, Ghada; Hassan, Syed Mustafa (EdTech Hub, 2025)
This report presents a rapid evaluation of AI-generated lesson plans currently being used in public schools in rural and urban Islamabad under the National Institute of Excellence in Teacher Education (NIETE). These centrally developed, scripted lesson plans are aligned with the national curriculum and built on the Gradual Release of Responsibility (GRR) model, with additional elements of the 5E and Inquiry-Based Learning (IBL) models in science, and the Concrete-Pictorial-Abstract (CPA) model in maths. Using a mixed-methods approach—including teacher surveys, focus group discussions, key informant interviews, and an expert rubric-based review—the study assesses the lesson plans' quality, relevance, and adaptability. Teachers expressed strong support for the lesson plans, especially in terms of reduced workload and structured delivery, though concerns were raised around flexibility, contextual responsiveness, and teacher agency. While the study does not evaluate student learning outcomes, it provides actionable insights and recommendations for improving the design, support, and implementation of AI-generated instructional tools, particularly as the programme scales to other provinces in Pakistan, such as Balochistan. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15077892 ZenodoArchiveConcept: 15077891 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1104 10.53832/edtechhub.1105 10.53832/edtechhub.1107 10.53832/edtechhub.1108 2405685:2PITNHGC 2405685:FR4GREKJ 2405685:XG7G3FDM 2405685:XKIEQVIQ
Keywords: _r:AddedByMyEducationEvidence

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13767575 ZenodoArchiveConcept: 13767574 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1050 10.53832/edtechhub.1060 2405685:K28H9QDG 2405685:ZAKFGN9M
Keywords: _r:AddedByMyEducationEvidence

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen